A CFD Investigation of the Effects of Fuel Split Fraction on Advanced Low Temperature Combustion: Comparing a Primary Reference Fuel Blend and Ethanol - Rahimi Boldaji, Mozhgan; Sofianopoulos, Aimilios; Mamalis, Sotirios; Lawler, Benjamin (Frontiers in Mechanical Engineering, 2018)
There is continuously growing interest in renewable biofuels for combustion engines to help reduce transportation energy consumption. In the present work, ethanol and a Primary Reference Fuel (PRF) were studied in an advanced LTC concept using CFD. A split injection strategy was used where the majority of the fuel was injected early during the intake stroke to create a well-mixed charge, while a portion of the charge was direct injected closer to ignition to induce forced thermal and equivalence ratio stratification in a strategy similar to partial fuel stratification (PFS). This way, the combustion process in LTC can be better controlled by staggering the autoignition process through mixture stratification. The unique characteristics of ethanol, such as its high latent heat of vaporization and reduced ϕ-sensitivity, result in unique features for a PFS-style advanced LTC mode, explored in this paper. A 3D CFD model with detailed chemistry was implemented in CONVERGE. The results showed that for both ethanol and PRF fuels, a split direct injection strategy lowers the peak heat release rate and elongates the combustion process compared to a single early direct injection due to the increased stratification. However, this effect was more pronounced for ethanol compared to PRF90 due to its higher latent heat of vaporization and reduced ϕ-sensitivity. For a 60%-40% split injection, the burn duration increased by 118% for ethanol and 91.6% for PRF90. The temperature, equivalence ratio, and OH mass fraction distributions illustrated that ethanol is primarily temperature-sensitive, while PRF90 shows a degree of ϕ-sensitivity in conjunction with temperature-sensitivity. The split direct injection of fuel creates an equivalence ratio and temperature distribution that are coupled due to the latent heat of vaporization of the fuel. For the PRF, these two effects are competing; whereas for the ethanol, the autoignition event is dictated by the thermal gradients since the fuel has a higher latent heat of vaporization and is not as ϕ-sensitive. Therefore, a PFS-style injection strategy is able to elongate the heat release rates more significantly with ethanol compared to a PRF.